Niemożliwe światy Justyny Bargielskiej. Lektura afektywna - Glosowitz, Monika (Śląskie Studia Polonistyczne, 2014)
The article is a result of an affective reading of poetry by Justyna Bargielska. Such analytical practice, amply utilizing tools proposed by theoreticians of the so-called “affective approach”, becomes first and foremost a reconstruction of affective strategies, which found poetic spaces. A feature representative of Bargielska’s works are descriptions of impossible worlds, in which she reveals mechanisms of perception and creation, at the same time exposing normative functions of language and emphasizinh its affective potential. In thusly outlined reading model, the participation of another subject – a reader, following “conceptual entities” along a semiotic trajectory – is also problematized as an experience, which stems from an autonomy of fictionalization awarded to the reader.